Pengaruh Breathing Exercise Terhadap Kesehatan Fisik Lanjut Usia - Putri, Khadiah Andini, Isnaini Herawati, SSt. FT, M. Sc (2018)
Background: Elderly, a person will experience changes in terms of physical, cognitive, and in his psychosocial life. This emphasizes the issue of life expectancy and physical health. Respiratory devices can increase respiratory strength to improve lung function. It can help with respiratory diaphragms and deep breathing to increase oxygen saturation more, reduce the work of helpful muscles and help us enjoy their own breathing pattern. Purpose: To determine the effect of breathing exercise on physical health. Methods: Quasi experimental research sampling technique using purposive sampling, the number of samples in this study were 26 respondents. The result of this research is paired sample t test. Result: Analysys of data using paired sample t test showed the pulse, respiration and VO2 max which had significant effect on the insignificant performance. Conclusion: There are symptoms of breathing exercise on physical health.